Wykorzystanie funduszy polityki strukturalnej Unii Europejskiej na Dolnym Śląsku w pierwszym okresie programowania - Rymarczyk, Jan (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
In the period 2004-2006 Lower Silesia was taking advantage of the finances of the European Community within the confines of preaccession aid. Then the region became the member of this organization. The first group created mainly the funds PHARE, ISPA, SAPARD and so called the Initiatives of European Community (Equal, Interreg). They had to strengthen a balanced development of region but because of their relatively small dimension they didn't bring about significant effects. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1173, s. 286-296